MLVA16 typing of Portuguese human and animal Brucella melitensis and Brucella abortus isolates. - Ana Cristina Ferreira (Public Library of Science (PLoS), 2012)
To investigate the epidemiological relationship of isolates from different Portuguese geographical regions and to assess the diversity among isolates, the MLVA16(Orsay) assay (panels 1, 2A and 2B) was performed with a collection of 126 Brucella melitensis (46 human and 80 animal isolates) and 157 B. abortus field isolates, seven vaccine strains and the representative reference strains of each species. The MLVA16(Orsay) showed a similar high discriminatory power (HGDI 0.972 and 0.902) for both species but panel 1 and 2A markers displayed higher diversity (HGDI 0.693) in B. abortus compared to B. melitensis isolates (HGDI 0.342). The B. melitensis population belong to the "Americas" (17%) and "East Mediterranean" (83%) groups. No isolate belonged to the "West Mediterranean" group. Eighty-five percent of the human isolates (39 in 46) fit in the "East-Mediterranean" group where a single lineage known as MLVA11 genotype 116 is responsible for the vast majority of Brucella infections in humans. B. abortus isolates formed a consistent group with bv1 and bv3 isolates in different clusters. Four MLVA11 genotypes were observed for the first time in isolates from S. Jorge and Terceira islands from Azores. From the collection of isolates analysed in this study we conclude that MLVA16(Orsay) provided a clear view of Brucella spp. population, confirming epidemiological linkage in outbreak investigations. In particular, it suggests recent and ongoing colonisation of Portugal with one B. melitensis lineage usually associated with East Mediterranean countries.